Features of the Femoral Proximocaudal Joint Capsule Insertion Among Canids. Issue 12 (9th September 2019) - Lawler, Dennis; Tangredi, Basil; Owens, Jerry; Evans, Richard; Widga, Christopher; Martin, Terrance; Smith, Gail; Schulz, Kurt; Kohn, Luci
ABSTRACT: This observational study was conducted to evaluate the anatomic relationship between the proximocaudal femoral joint capsule insertion and the femoral caudolateral curvilinear osteophyte (CCO), across ancient and modern domestic and non‐domestic canids. Museum specimens of proximal femora were screened for presence of remnant enthesophytes of the caudal joint capsule insertion (first inclusion criterion) and then for the CCO (second inclusion criterion). The initially screened population included 267 dry bone specimens: Six Canis species, hybrid coyote × domestic dog, and five vulpines (three Vulpes species, one Urocyon, and one Nyctereutes ). Proximocaudal joint capsule insertion remnant enthesophytes were limiting at n = 19 specimens: Seven ancient domestic dogs, four modern coyotes, two ancient coyotes, two modern hybrid coyote × dog, two modern red foxes, and two modern raccoon dogs. The joint capsule enthesophytes are associated with inflammation, but are observed far less frequently than the CCO. The CCO is seen radiographically but is visible more frequently by direct inspection. The primary inclusion criterion necessarily was a visible caudal joint capsule insertion; spatial relationships of the CCO can be assigned with confidence only when a capsule insertion line can be recognized clearly. We demonstrate that the anatomic CCO associates with the joint capsule insertion being nonspecific and species‐independent. A joint capsule insertion‐CCO spatial relationship across species is an important new observation, strongly indicating that both are pathological features. Our data indicate need for new research to characterize the canid coxofemoral joint and its overt and incipient pathology in a phylogenetic context. Anat Rec, 302:2164–2170, 2019. © 2019 American Association for Anatomy